Neotypification of Allium senescens var. minus (Amaryllidaceae) - Oh, Seung-Hwan; Ji, Seong-Jin; Choi, Hyeok-Jae (Phytotaxa, 2018)
The genus Allium Linnaeus (1753: 294) is one of the largest genera of monocots (Sinitsyna et al. 2016). Currently, the number of species within the genus is estimated at 920 (Seregin et al. 2015). In the Korean peninsula, twenty species and two varieties are reported, of which four species and two varieties are endemic to the country (Choi & Oh 2011).